2021
DOI: 10.3390/ijerph18063009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Injuries in First Division Spanish Women’s Soccer Players

Abstract: The epidemiology of injuries in female soccer has been studied extensively in several national leagues. Even so, data on the first division Spanish league are limited. The objective of this study was to describe the epidemiology of the first division of the Spanish Women’s Soccer League and to analyze data in relation to game position, circumstance, or the moment of injury. Fifteen teams and 123 players participated in the study. Players’ characteristics and their injuries (location, type, diagnosis, circumsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…A recently published systematic review and meta-analysis reported injury incidences during training and matches of 3.1 and 19.5 per 1000 h, respectively [66]. Another study performed among female first division female football players reported a similar match injury incidence (19.0 per 1000 h) but a slightly lower number of injuries during training exposures (1.7 per 1000 h) [10]. Regarding injury burden, the results in the present research are partially in accordance with those previously reported in the literature by Sprouse et al [63].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A recently published systematic review and meta-analysis reported injury incidences during training and matches of 3.1 and 19.5 per 1000 h, respectively [66]. Another study performed among female first division female football players reported a similar match injury incidence (19.0 per 1000 h) but a slightly lower number of injuries during training exposures (1.7 per 1000 h) [10]. Regarding injury burden, the results in the present research are partially in accordance with those previously reported in the literature by Sprouse et al [63].…”
Section: Discussionmentioning
confidence: 98%
“…Football has been described as a demanding sport from the neuromuscular [1,8] and physiological [9] perspectives leading to female athletes having a high injury risk with subsequent time off from competition [2] and an inevitable impact on the player's physical and physiological health [10]. Injuries among female football players have been reported to range from 9.1 to 24 injuries per 1000 h of exposure [11], which is less than males in terms of incidence, but with a greater associated injury burden due to the more severe nature of the resulting injuries, especially ACL ruptures [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Horan D and colleagues were in the same line with their ndings from the Irish Women's National League (54), reporting a 7.9 injuries / 1000 h exposure overall injury incidence ratio with an even higher difference (7.5 times) in between match (192 / 1000 h) and training (2.5 / 1000 h). Another recent study from the rst division of Spanish Women's Soccer League (53), reported an injury incidence ration of 3.65 injuries / 1000 h with an even higher match versus training injury incidence ratio (19.02 / 1000 h and 1.70 / 1000 h, respectively). An earlier 2005 study from the German's National League (27), reported an injury rate of 6.8 injuries / 1000h of exposure, while being as high as 23.3 / 1000 in match hours and 2.8 / 1000 hours of training.…”
Section: Incidence Rate Of Overall Injurymentioning
confidence: 96%
“…Many studies have been investigating soccer-related injuries played in various major soccer leagues (27,28,(52)(53)(54), many of which show signi cant differences across countries in the frequency of injuries. In this study, the elite women's soccer league's overall injury rate was observed in Kosovo is 3.21 (CI: 1.24, 3.27), which was surprisingly lower than in other studies.…”
Section: Incidence Rate Of Overall Injurymentioning
confidence: 99%